Bundling Bridge and Other Highway Projects: Patterns and Policies. Issue 12 (December 2018) - Qiao, Yu Julie; Fricker, Jon D.; Labi, Samuel; Mills, Trevor
The concept of project bundling—combining multiple projects into a single contract—continues to gain momentum. Unanswered questions from past studies include how to quantify project bundling benefits. This paper addresses the issue using a data-driven approach that involves initial comparisons of the unit average project costs of single and bundled projects, preliminary investigations of the potential influential variables of project cost, the development of project cost statistical models, and an analysis of past and possible future bundling strategies. The study found that the primary drivers of project cost include the project size (economies of scale), bundling strategy (economies of bundling), and bidding market conditions (economies of competition). It is also shown that the similarity between different project types in terms of their constituent pay items is an influential factor on project cost. The study confirmed that larger contracts yield economies of scale but may also lead to less competition (discouraging all but the largest firms from bidding). This finding suggests the existence of a contract-size threshold beyond which the unit project cost increases with increasing project cost. By analyzing past bundling strategies, the study identified the most frequent combinations of work categories in the past bundled contracts. The study also carried out scenario analyses using hypothetical bundling strategies applied to actual past projects and determined that bundling projects using a carefully designed strategy can yield significantly reduced overall contract costs.